Exploring African Holism with Respect to the Environment. (1st November 2010) - Behrens, Kevin
Abstract : Contrary to a pervasive presumption of anthropocentricism in African thought, I identify an emphasis on the interrelatedness or interconnectedness of everything in nature, and argue that this is best construed as a rejection of anthropocentrism, and as something similar in conception to, and yet distinct from, holist perspectives. I propose that this strand of African thought, suitably reconstructed, should be construed as providing the basis for a promising non-anthropocentric African environmentalism. I name this position 'African Relational Environmentalism', and suggest that it is what distinguishes this position from holism that can most enrich environmental ethics.